# If x = a sec θ + b tan θ a and y = a tan θ + b sec θ, then prove that x2 – y2 = a2 – b2.

Taking LHS =x2 – y2

Putting the values of x and y, we get

(a sec θ + b tan θ)2 – (a tan θ + b sec θ)2

= a2 sec2θ + b2 tan2θ + 2ab sec θ tan θ – a2tan2θ – b2 sec2θ – 2ab sec θ tan θ

= a2 (sec2θ – tan2θ) – b2 (sec2θ – tan2θ)

= a2 – b2 [ 1+ tan2 θ = sec2 θ]

=RHS

Hence Proved

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Related Videos
Champ Quiz | Trigonometric Identities33 mins
Trigonometric Identities33 mins
NCERT | Trigonometric Identities52 mins
Quiz | Task on Trigonometric Ratios46 mins
Algebraic Identities48 mins
Quiz | Practice Important Questions on Trigonometrical Identities46 mins
Quiz on Trigonometric Ratios31 mins
T- Ratios of Specified Angles58 mins
Trick to learn all Trigonometric Formulae28 mins
Testing the T- Ratios of Specified Angles57 mins
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
view all courses